Design as a Significant Component in Public Policy Observatories in Colombia - López Ospina, Sebastián (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
This article addresses the concept of design as an interdisciplinary element that seeks to recognize itself as a vehicle for raising awareness of the processes of socialization in observatories that aim to generate an impact in a specific community. The design seen as knowledge must from its formalization be remembered as a tool available to people who, in its manifestation (reification / function) goes into the background to be recognized as a cognitive act that leads to significant instances. Therefore, the following premise is planned: How does the design contribute to the construction of awareness in the processes of socialization of the observatory in public policy of fiscal control?